Product attributes and consumer preference: the case of common beans in Zambia - Atilola, Bolanle (Kansas State University, 2018)
Beans play a major role in addressing malnutrition and poverty in Africa. Hence, several studies have been conducted over the last two decades on beans attributes in various African countries, including Zambia. The similarity of these studies is their emphasis on the importance of including consumer preferences in the beans supply chain. This study attempts to contribute to informing the bean supply chain about bean attributes and consumer characteristics influencing beans consumption so that downstream stakeholders can effectively seize the embedded opportunities in the bean supply chain. Data used in this study were obtained from 900 surveyed households in Lusaka, Zambia and analyzed using a logit model. The study evaluated three attributes of beans: gravy quality; cooking time; and grain size. In addition, it assessed the price of beans associated with these attributes. The study sought to determine how these attributes influenced consumer preference for specific color beans. Results show that gravy quality, cooking time and price are important bean attributes influencing consumer preference for purple, mixed yellow and yellow bean while grain size has no statistically significant effect. The study also found that gender, education, and employment status of the household head or person purchasing food for the household, as well as the household’s child dependency ratio, dual household income, residential area and perception of the bean food group’s importance to consumers’ nutritional security were statistically significant in their effect on preference for purple, mixed yellow and yellow beans. The study’s results contribute to downstream stakeholders’ efforts to improve their own decisions in identifying the market segments to engage in. For example, bean breeders, producers, and traders might optimize limited resources available for their activities by investing in products that promise large markets to use volume to overcome any price disadvantage regarding profitability. Similarly, they may also invest in high-value low volume products that could also provide them with acceptable profitability. The option used would depend on their location and their own resource situation.
Keywords: Consumer preference; Product attributes; Logit model; Common beans; Zambia